Individual and Community-Level Factors Associated with Caesarean Section in Haiti: Secondary Analysis of Data from the 2016–2017 Haitian Demographic and Health Survey - Aujogue-, J (BioMed Central Ltd, 2023)
Introduction: For several decades, the rate of caesarean section (CS) has been increasing in the world. In some countries, the CS rate is below the WHO recommended range (10–15%), while in other countries, it is significantly higher. The aim of this paper was to identify individual and community-level factors associated with CS in Haiti. Methods: Secondary data analysis was conducted on nationally representative cross-sectional survey data from the 2016–2017 Haitian Demographic and Health Survey (HDHS). The analysis was restricted to 6303 children born in 5 years prior the survey (of the interviewed women). The study population’ characteristics, and the prevalence of CS were analysed using descriptive analysis (univariate/bivariate). In addition, multilevel binary logistic regression analysis was performed to identify factors associated with CS. Both descriptive and multivariate analysis were conducted using STATA 16.0 software (Stata Corp, Tex, USA). Statistical significance was declared at p < 0.05. Results: The overall prevalence of CS delivery was estimated at 5.4% (95% CI 4.8–6.0) in Haiti. Results also revealed that mothers aged 35 and above (aOR = 1.38; 95% CI 1.00–1.96); who attended secondary (aOR = 1.95; 95% CI 1.39–2.76) and higher education level (aOR = 3.25; 95% CI 1.92–5.49); who were covered by health insurance (aOR = 2.57; 95% CI 1.57–4.19); with less than 3 children (aOR = 4.13; 95% CI 2.18–7.85) or 3–4 children (aOR = 2.07; 95% CI 1.09–3.94); who received 9 or more antenatal visits (aOR = 2.21; 95% CI 1.40–3.50) were significantly more likely to deliver by CS. Children in communities with high preponderance of private health facilities had greater odds to be delivered through CS (aOR = 1.90; 95% CI 1.25–2.85). Furthermore, children with an average birth weight (aOR = 0.66; 95% CI 0.48–0.91) were less likely to be delivered through CS than their counterparts with high birth weight. Conclusions: While the CS prevalence was low in Haiti, it masks significant geographic, social and economic disparities. To better develop and implement maternal and child health programs that address CS deliveries, the government authorities and NGOs operating in the field of women’s health in Haiti should take these disparities into account. © 2023, The Author(s).